Synthesis, characterization and DNA binding properties of Schiff base derivatives and Ru(II) complexes - Elmali, Fikriye Tuncel (ELSEVIER, 2022)
Schiff base ligands were synthesized by condensation of 5-amino-1,10-phenanthroline with 4hydroxybenzaldehyde (L1) and decanal (L2). Ruthenium (II) metal complexes (L1-Ru(II), L2-Ru(II)) were prepared in good yield from the reaction of the ligands with the bis(2,2'-bipyridine)ruthenium(II) dichloride. Structures of synthesized compounds were characterized using elemental analyze, FTIR, UV Visible, H-1 NMR and mass spectra. The DNA-binding properties of the ligands and complexes with calf thymus DNA was investigated by spectroscopic, gel electrophoresis and viscosity measurement. The interaction of the ligands and ruthenium complexes with calf tymus DNA (CT-DNA) have been demonstrated using electronic absorption titration method. Based on the UV-Vis spectroscopy, binding constants of the synthesized compounds with CT-DNA calculated. From the results, it is observed that L1 and L1-Ru(II) bind to CT-DNA via groove binding and electrostatic mode and L2 and L2-Ru(II) bind to CT-DNA via intercalation. Kb values of L1 and L1-Ru(II) with CT-DNA were calculated as 5.2 x 10(5) M-1 and 4.8 x 10(6) M-1, respectively. Absorption spectral study indicated that L2 and L2-Ru(II) have intrinsic binding constant (Kb) in the range of 3.8 x 10(5)-3.7 x 10(6) M-1. The results show that the complexes have more binding ability than the ligands. (c) 2022 Elsevier B.V. All rights reserved.
Keywords: Schiff base; Ru (II) complex; DNA binding; Amino-phenanthroline; LIGANDS SYNTHESIS; CRYSTAL-STRUCTURE; SPECTRAL CHARACTERIZATION; METAL-COMPLEXES; CLEAVAGE; CYTOTOXICITY; RUTHENIUM; CU(II); DFT; PHOTOCLEAVAGE; Chemistry